Відповідь:
Пояснення:
1. б)
2. x×(a-y)=ax-xy
3. 2а-4=2(а-2)
4 а) (5х-1)×(1+2х)-7х=5х+10[tex]x^{2}[/tex]-1-2х-7х=-4х+10[tex]x^{2}[/tex]-1=10[tex]x^{2}[/tex]-4х-1
б) 2b×(b-3)-5b×(b-7)=2[tex]b^{2}[/tex]-6b-5[tex]b^{2}[/tex]-35b=-3[tex]b^{2}[/tex]-41b
5. a) 4ab+8a=4a×(b+2)
б) am-b+m-ab=m×(a+1)-b×(1+a)=(a+1)×(m-b)
6. (a+3)×(a-2)-a×(a+9)+6=[tex]a^{2}[/tex]+2a+3a-6-[tex]a^{2}[/tex]-9a+6=-2a+3a-6-9a+6=-2a+3a-9a=-8a
7.3(5x-1)=4(4x-8)
15x-3=16x-32
15x-16x=-32+3
-x=-29
x=9
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Відповідь:
Пояснення:
1. б)
2. x×(a-y)=ax-xy
3. 2а-4=2(а-2)
4 а) (5х-1)×(1+2х)-7х=5х+10[tex]x^{2}[/tex]-1-2х-7х=-4х+10[tex]x^{2}[/tex]-1=10[tex]x^{2}[/tex]-4х-1
б) 2b×(b-3)-5b×(b-7)=2[tex]b^{2}[/tex]-6b-5[tex]b^{2}[/tex]-35b=-3[tex]b^{2}[/tex]-41b
5. a) 4ab+8a=4a×(b+2)
б) am-b+m-ab=m×(a+1)-b×(1+a)=(a+1)×(m-b)
6. (a+3)×(a-2)-a×(a+9)+6=[tex]a^{2}[/tex]+2a+3a-6-[tex]a^{2}[/tex]-9a+6=-2a+3a-6-9a+6=-2a+3a-9a=-8a
7.3(5x-1)=4(4x-8)
15x-3=16x-32
15x-16x=-32+3
-x=-29
x=9